The multifaceted potential of TPT1 as biomarker and therapeutic target - Gelan Miao; Yulian Yang; Xuelian Yang; Dexiu Chen; Li Liu; Xianying Lei (Heliyon, 2024)
Tumor Protein Translationally-Controlled 1 (TPT1) is a highly conserved gene found across eukaryotic species. The protein encoded by TPT1 is ubiquitously expressed both intracellularly and extracellularly across various tissues, and its levels are influenced by various external factors. TPT1 interacts with several key proteins, including p53, MCL1, and immunoglobulins, highlighting its crucial role in cellular processes. The dysregulation of TPT1 expression has been documented in a wide range of diseases, indicating its potential as a valuable biomarker. Additionally, targeting TPT1 presents a promising approach for treating and preventing various conditions. This review will assess the potential of TPT1 as a biomarker and evaluate the effectiveness of current strategies designed to inhibit TPT1 in disease contexts.